Perbedaan Efektifitas Pemberian Jus Belimbing Wuluh dan Jus Mentimun terhadap Tekanan Darah Lansia Penderita Hipertensi - Rahayu, Siti Suci; Martyastuti, Nonik Eka; Vianti, Remilda Armika; Sulistyowati, Dina Indrati Dyah (JURNAL KEPERAWATAN MERSI, 2024)
Background: The most common diseases experienced by the elderly are Diabetes Mellitus and Hypertension. One of the non-pharmacological treatments for hypertension is by consuming starfruit juice and cucumber juice. Starfruit and cucumber both contain potassium and are diuretics that can lower blood pressure. Objective: This study aims to determine the difference in the effectiveness of giving star fruit juice and cucumber juice on blood pressure in elderly patients with hypertension. Methods: This study used a quasi-experiment method with a pretest and posttest control group design. This design involves 2 groups (two groups) with a sample of 32 people (16-star fruit juice and 16 cucumber juice group). Star fruit juice and cucumber juice were drunk in the morning before meals for 7 consecutive days with a dose of 100 grams of star fruit and 200 ml of water, 200 grams of cucumber, and 150 ml of water. Results: The results showed that a beverage of cucumber juice lowers significantly systolic blood pressure (p=0.000) and diastolic blood pressure compared with a beverage of star fruit juice (p=0.000). Conclusion: Giving a combination of star fruit juice and cucumber juice for 7 days at a dose of 100 grams of star fruit and 200 ml of water, 200 grams of cucumber, and 150 ml of water is more effective in reducing blood pressure compared to giving only cucumber juice.